The Role of Health System to Support PMTCT Program Implementation in Jayawijaya Regency - Trisnawati, Lea Meirina; Thabrany, Hasbullah (Journal of Indonesian Health Policy and Administration, 2015)
The incidence of HIV and AIDS in Indonesia continues to increase. The possibility of mother to child transmission will be greater if intervention is not performed. The purpose of this study is to assess the role of health systems in health and non-health sector affecting the implementation of PMTCT. This qualitative research took place in Jayawijaya. Primary data collection was conducted through in-depth interviews, and observation. Secondary data was derived from the survey of health facilities conducted in Papua. We interviewed eleven (11) informants. The results of this study confirmed that the implementation of PMTCT was still inadequate, only 64% of the health services in Jayawijaya provide PMTCT services. Considering the vast area and the difficulty of access to health services, local government should undertake expansion of comprehensive PMTCT services, provide antiretroviral drugs for pregnant women, and reagents, as well as psychosocial support to PLHIV.